Forced Degradation studies of Naringenin: Isolation, Identification and Structural Elucidation of Stress Degradation Products using NMR, FTIR, Mass spectroscopy and Prep-HPLC - Pawar, Tarak; Tayade, Rajratna P.; Gawade, Anil S. (Asian Journal of Chemistry, 2026)
This study presents the forced degradation study of the antioxidant molecule naringenin (NNG) under various stress conditions following ICH guidelines Q1A(R2). Significant degradation under basic and oxidative stress were observed. It is quite stable in acidic, photolytic and thermal conditions. Under basic stress conditions, two major degradation products, NNG-DP1 and NNG-DP2, were obtained, which are isomers of each other. Under oxidative stress, one major degradation product, NNG-DP1, was observed, structurally similar to the E-isomer obtained under basic stress conditions. The degradation compounds were isolated using chromatographic separation, purified and characterized utilizing advanced analytical methods, including (1H, 13C, D2O) NMR, FT-IR, COSY, NOESY and mass spectrometry techniques. Repeatability of the self-developed HPLC method was determined at 20-120 µg/mL, obtaining an RSD (%) < 2.0 and accuracy > 98%. The mean recovery, LOD and LOQ values were found to be 98.25-102.88%, 0.1 µg/mL and 1.0 µg/mL, respectively. A probable mechanism for the formation of the major degradation products was also proposed.